Influence of carbon source on in vitro tuberization and growth of white yam (Dioscorea rotundata Poir.) - Ng, S.Y.C.; Mantell, S.H. (1998)
The response of white yam (Dioscorea rotundata Poir.) nodal cuttings to eight different carbon sources (sucrose, glucose, mannose, maltose, galactose, fructose, lactose, and sorbitol) at two concentrations (3 and 5%) in modified Murashige and Skoog medium was investigated. The number of nodes per plant (NNP), plantlet fresh weight, number of leaves per plant (NLP), percentage tuberization, number of micro-tubers per plant (NTP), and micro-tuber weight per plant (TWP) were significantly different among the carbon sources (P < 0.01). There were no significant differences in terms of micro-tuber weight per tuber and plant dry matter content. In terms of NNP and NLP, fructose, glucose, mannose, and sucrose at 3 and 5%, and sorbitol at 5% were comparable. However, nodal cuttings were unable to produce tubers in media containing sorbitol. All the explants cultured in 5% sucrose, 5% fructose, and 3 and 5% mannose produced micro-tubers. The NTP ranged from 0.9 (3% mannose) to 1.8 (5% sucrose), while 5% glucose gave the highest TWP, followed by 5% sucrose. The best carbon sources for in vitro tuberization were sucrose and fructose.